Anatomical, Cardiovascular, and Blood Gas Parameters in Dogs with Brachycephalic Syndrome - Dias, Maria Luíza de Melo; Morris, Carlos Fernando Matias; Moreti, Bruno Marques; Santos, Arthur Victor do Espírito; McManus, Concepta Margaret; Almeida, Ricardo Miyasaka de; Galera, Paula Diniz (Acta Scientiae Veterinariae, 2016)
Background: Brachycephalic syndrome is characterized by increased airflow resistance in upper airways due to the combinations of anatomical deformities such as stenotic nares, elongated soft palate, everted laryngeal saccules, and tracheal hypoplasia. There is little information in recent literature about assessment of anatomical, cardiovascular, and blood gases’ parameters of these animals at early stages of the syndrome. The purpose of this study was to characterize and to compare anatomical, cardiovascular, and blood gases’ parameters in young brachycephalic or dolichocephalic and mesocephalic dogs. Materials, Methods & Results: Twenty brachycephalic dogs (BG) and 20 dolichocephalic and mesocephalic dogs (CG), aged up to 5 years, were included in the study. Anatomical abnormalities, systolic (SAP), mean (MAP), and diastolic (DAP) arterial blood pressure were recorded. Blood gas analysis and complete blood counts (CBC) were analyzed. Doppler echocardiography, electrocardiography, ambulatory electrocardiography, and thoracic and cervical radiographs were evaluated. The diameter of the nares in BG was lower when compared to CG (0.23 ± 0.08 versus 0.56 ± 0.05 cm, P < 0.001). The SaO2 was lower (P < 0.001) and MAP was higher in BG (P = 0.05). All brachycephalic dogs had sinus arrhythmia (SA), and 15 (75 %) of these showed SA higher than 20% variation between adjacent RR intervals, whereas in CG, 17 (85%) of animals presented SA and 13 (65%) of these showed SA higher than 20 % variation between adjacent RR intervals. The smallest opening of the nostril, in brachycephalic dogs, was accompanied by a lower SaO2 and higher MAP. Results of this study suggest that young brachycephalic dogs have lower SaO2 and higher MAP when compared with dolichocephalic and mesocephalic dogs. Discussion: The most relevant aspect of this survey was the confirmation that brachycephalic dogs have lower SaO2 and higher MAP when compared to non brachycephalic animals. Few studies correlate upper airway obstruction to cardiovascular and blood gas alterations. Although there were no significant differences between groups for PaO2 and AaDO2, the means for BG were lower and higher, respectively, than CG, showing that obstruction of airways may lead to lower PaO2 and higher AaDO2. In the present study, brachycephalic animals tended to have higher tHb, PCV, DAP, and MAP, and lower SaO2. Even with no significant differences between groups for tHb, PCV, and DAP, one can assume that young animals may not already have presented such alterations, but as the syndrome progresses, these types of abnormalities tend to develop. Hypoventilation results in significantly lower SaO2 in these animals, as observed in this study. All brachycephalic dogs in our study had SA and 2 (10%) showed sinus pauses of 4 s and 6 s duration, which demonstrates a stimulated vagal tone. The percentage of cervical soft tissue (CST) in brachycephalic dogs was proposed in an attempt to objectively measure the soft tissue concentrated in the neck region of these animals, which may be considered a risk factor for development of the syndrome. The CST percentage was higher in BG, probably due to the increased amount of adipose tissue in the neck of these animals, fact that can contribute to an increase in tracheal pressure and vascular resistance in the region. Therefore, alterations of brachycephalic syndrome result in significant cardiovascular and blood gas abnormalities in young brachycephalic dogs, as higher MAP and lower SaO2.